Cyclical and Market Determinants of Involuntary Part-Time Employment - Robert G. Valletta; Leila Bengali; Catherine van der List (Institute for the Study of Labor (IZA), 2016)
We examine the determinants of involuntary part-time employment, focusing on variation associated with the business cycle and variation attributable to more persistent structural features of the labor market. Our theoretical framework distinguishes between workers' decision to seek part-time work and employer demand for part-time work hours, emphasizing demand and supply determinants of involuntary part-time work such as workplace technology, labor costs, and workforce demographics. We conduct regression analyses using state-level panel and individual data for the years 2003-2014. The results show that the combination of cyclical variation and the influence of market-level factors can explain virtually all of the variation in the aggregate incidence of involuntary part-time employment since the Great Recession.
Keywords: J22; J23; 330; part-time employment; business cycle; supply and demand